Sources and assumptions for the vicarious calibration of ocean color satellite observations - Bailey, S.; Hooker, S.; Antoine, David; Franz, B.; Werdell, P. (Optical Socity of America, 2008)
Spaceborne ocean color sensors require vicarious calibration to sea-truth data to achieve accurate waterleaving radiance retrievals. The assumed requirements of an in situ data set necessary to achieve accurate vicarious calibration were set forth in a series of papers and reports developed nearly a decadeago, which were embodied in the development and site location of the Marine Optical BuoY (MOBY).Since that time, NASA has successfully used data collected by MOBYas the sole source of sea-truth data for vicarious calibration of the Sea-viewing Wide field-of-view Sensor (SeaWiFS) and Moderate Resolution Imaging Spectroradiometer instruments. In this paper, we make use of the 10-year, global time series of SeaWiFS measurements to test the sensitivity of vicarious calibration to the assumptions inherent in the in situ requirements (e.g., very low chlorophyll waters, hyperspectral measurements). Our study utilized field measurements from a variety of sources with sufficient diversity in data collection methods and geophysical variability to challenge those in situ restrictions.We found that some requirements could be relaxed without compromising the ability to vicariously calibrate to the level required for accurate water-leaving radiance retrievals from satellite-based sensors.